Evaluation of 11 SARS-CoV-2 antibody tests by using samples from patients with defined IgG antibody titers - Nina Lagerqvist (Nature Portfolio, 2021)
Abstract We evaluated the performance of 11 SARS-CoV-2 antibody tests using a reference set of heat-inactivated samples from 278 unexposed persons and 258 COVID-19 patients, some of whom contributed serial samples. The reference set included samples with a variation in SARS-CoV-2 IgG antibody titers, as determined by an in-house immunofluorescence assay (IFA). The five evaluated rapid diagnostic tests had a specificity of 99.0% and a sensitivity that ranged from 56.3 to 81.6% and decreased with low IFA IgG titers. The specificity was > 99% for five out of six platform-based tests, and when assessed using samples collected ≥ 22 days after symptom onset, two assays had a sensitivity of > 96%. These two assays also detected samples with low IFA titers more frequently than the other assays. In conclusion, the evaluated antibody tests showed a heterogeneity in their performances and only a few tests performed well with samples having low IFA IgG titers, an important aspect for diagnostics and epidemiological investigations.